Analisis Kebutuhan Tenaga Kerja Berdasarkan Metode Workload Indicators Staffing Need (Wisn) Di Depo Farmasi Rawat Jalan Rsud Arifin Achmad Provinsi Riau - Tiara Tri Agustini; Septi Muharni; Yola Marina Dwiputri (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
One of the health service facilities is a hospital. The success of the hospital in carrying out its functions is influenced by several factors including the most dominant being human resources. Planning for the need for manpower in outpatient pharmacy depots needs to be considered because it plays a role in direct service to patients which will affect the quality of hospital services. Method Workload Indicators Staffing Need (WISN) is a indicator to calculate workforce requirements based on real workload undertaken by the workforce in each work unit in health care facilities including hospitals. This study aims to determine workforce requirements in outpatient pharmacy depots RSUD Arifin Achmad Provinsi Riau. This study is a research observations, which is descriptive using interview techniques. The sample in this study were informants who were selected by purposive sampling. ased on the calculation results, the number of total workforce required is 18 workforce while the workforce in in outpatient pharmacy depot 16 workforce. so that there is a shortage of 2 workforce. The calculation of the WISN ratio obtained was 0.88 (<1), meaning that the need workforce based on workload is still a shortage of workforce in outpatient pharmacy depots.